Integrated Fare Systems for Local Public Transport: A Regional Prospective - Fabio Bianchi (European Regional Science Association (ERSA), 2012)
Studies carried out so far in the literature of transport economics have focused almost exclusively on the analysis of the costs of transportation companies (both public and private) and the effects of the planning of services operated by rail or bus, aiming at reducing their costs. During the last twenty years many European metropolitan areas, however, have developed an integrated tariff system to allow easier access to public transport for citizens. The paper is focused on the main successful attempts in transport fare integration among Europe which showed that any integrated system consists of one essential element: the zoning of the area. While the ticket price depends on economic variables such as income, the demand and the supply of services, zoning is closely tied to both the conformation of the territory and the form of government of the metropolitan area.. Regarding the zoning of areas subject to tariff integration, planning strategies that have been used in Europe correspond to four recurring criteria. These criteria do not seem to be independent of the political choices of actors who co-founded the metropolitan area where there an integrated tariff is in operation. Almost all the cities seemed to follow a common history in strategic planning and the main factor coincides with the role played by institutional actors and, above all, by the authority which held the leadership. In Region Lombardy a new integrated system is being set up which will coordinate seven local authorities; the enabling factor is based on an innovative technological platform that allows citizens to use their ID smartcard to load tickets and subscription. The fare integration is certainly an evolution of pricing in local public services, particularly in two areas: it allows a more efficient planning of transport services and the increase of more customers by simplifying the access to the system. A further element in favor of integrated systems is the change in the inter-institutional relations between the entities that are part of the metropolitan area whose close collaboration and the resulting best practices are also applicable to other public services than transportation.On the other hand, the integration confirms and amplifies the distortion sometimes caused by errors in the planning of public transport, beginning with some subsidies that are not entirely effective and consistent with the objectives publicly declared.
Keywords: R48; 330; public transport; transport fares; mobility governance; regional planning; eGovernment